Diversity of Soil Insects in Coal Post Mining Land of PT. Bukit Asam Tbk in Tanjung Enim - Paserena, Karinda Dwi; Damiri, Nurhayati; Setyawan, Dwi (Sriwijaya Journal of Environment, 2024)
Coal mining activities carried out openly can have a negative impact on the environment. One of the environmental damages that occurs is the loss of habitat for soil-level insects. This research was conducted to identify the diversity of soil surface insect species in post-coal mining land of PT. Bukit Asam Tbk Tanjung Enim IUP Banko Barat at various ages of reclamation. Soil surface insect samples were collected using the pitfall trap method which was carried out for 1x24 hours. The results showed that the highest presence of soil surface insect species occurred in aged 6 years with a total of 128 individuals and was dominated by the order Hymenoptera. The species diversity index in post-coal mining land aged 6 years, namely 1.51, is classified as moderate. The lowest presence of soil surface insects occurred in aged 2 years with a total of 24 individuals. The species diversity index in post-coal mining land aged 2 years, namely 0.85, is relatively low. Thus, the research results show that the diversity of surface soil insects is influenced by the age of reclamation. The longer the land is managed, the higher the index of diversity of soil surface insect species in post-coal mining land.